Electrically controlled release of 5-fluorouracil from conductive gelatin methacryloyl-based hydrogels - ALEMDAR YAYLA, NESLİHAN (WILEY, 2019)
Herein, electro-responsive hydrogels were obtained by incorporation of poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT/PSS) into the gelatin methacryloyl (GelMA) by using photopolymerization technique. Hydrogels were characterized by FTIR and scanning electron microscopy analyses. Cytotoxicity tests were performed by L929 cell lines to determine cell compatibility. Swelling tests were conducted to investigate the water uptake capacity of hydrogels. 5-fluorouracil (5-FU) was selected as a model drug as it is known as a topical drug for some skin cancer type treatment. The release of 5-FU from the hydrogel was provided in efficient and controlled manner at simulated skin cancer (pH = 5.5) and under 0 and 1.5 V. The simulated drug delivery experiments conducted in vitro revealed that the drug releasing amount was higher when voltage is applied to the hydrogels. All results visualized that the obtained GelMA-based PEDOT/PSS hydrogels with enhanced electrical properties could be a potential candidate as an electrically sensitive drug carrier for treatment of skin cancer in the future applications. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 46914.
Keywords: electrically conductive hydrogels; electroresponsive drug delivery; skin cancer treatment; 5-fluorouracil; CONTROLLED DRUG-DELIVERY; MECHANICALLY ROBUST; SKIN-CANCER; IN-VITRO; SYSTEMS; COMPOSITES; NANOFIBERS; VIVO